Gamification for Arabic Natural Language Processing: Ideas into Practice - Zeroual, Imad; El Kah, Anoual; Lakhouaja, Abdelhak (Transactions on Engineering and Computing Sciences, 2017)
Gamification is a novel IT development that focuses on how to address the use of games and apply game design techniques in a non-gaming context. Recently, it has significantly attracted several researchers’ attention concerned with different fields such as education, business, and information retrieval, among other fields. Most Natural Language Processing (NLP) applications use large accurately labelled data sets to achieve good performance, but these data sets are hard to obtain. The standard method to produce labelled data has been through manual labour that demands a strong engagement and a heavy financial participation. For these reasons, gamification may offer smooth possibilities for wide improvements in this field. However, gamification by itself may not yield the widely-expected results if the incentives are not strong motivators. Further, based on a previous experience, we strongly believe that even financial incentives are not enough for the participants to increase their contributions. Therefore, we could incentivise the participants, through gamification, and through their need for language acquisition. Thus, language-based games are adopted in this project as a direct incentive and a stronger engagement to ensure the benefits for both NLP practitioners and the language learners. In this paper, we present the first Arabic project that targets all the means to promote and explore the possibilities for research and practical applications of using games and gamification for Arabic NLP. Here, we shed light over the advantages of using a gamified approach in corpus annotation, named entity recognition, and word sense disambiguation.